2017
DOI: 10.1021/acs.langmuir.7b02813
|View full text |Cite
|
Sign up to set email alerts
|

Micellization and Partition Equilibria in Mixed Nonionic/Ionic Micellar Systems: Predictions with Molecular Models

Abstract: In practical applications, surfactant solutions are mostly used in mixtures of nonionic and ionic surfactants because they have improved characteristics compared to those of single surfactant solutions. By adjusting the composition of the micelles and the pH value, the solubilization of solutes can be enhanced. Nevertheless, the partitioning of solutes between nonionic/ionic mixed micelles and the aqueous phase is studied to a much lesser extent than for single surfactant solutions. Theoretical methods to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…It could be seen that the oil/aqueous IFT values of 6501 or AGS alone were all larger than 0.01 mN m −1 at 50 and 70 °C, which indicated that using 6501 or AGS alone could not achieve high EOR. This result was consistent with the existing conclusion that the EOR effect of an independent surfactant was not good enough (Vilasau et al, ; Yordanova et al, ). The oil/aqueous IFT values first decreased and then increased with the decrease of mass ratio of 6501 to AGS, and all were lower than 0.01 mN m −1 when the mass ratio of 6501:AGS was in the range from 2.86:1 to 2.19:1 regardless of whether the temperature was at 50 or 70 °C, indicating that 6501 and AGS have a very good synergistic effect (Jin et al, , , b, ).…”
Section: Resultssupporting
confidence: 93%
“…It could be seen that the oil/aqueous IFT values of 6501 or AGS alone were all larger than 0.01 mN m −1 at 50 and 70 °C, which indicated that using 6501 or AGS alone could not achieve high EOR. This result was consistent with the existing conclusion that the EOR effect of an independent surfactant was not good enough (Vilasau et al, ; Yordanova et al, ). The oil/aqueous IFT values first decreased and then increased with the decrease of mass ratio of 6501 to AGS, and all were lower than 0.01 mN m −1 when the mass ratio of 6501:AGS was in the range from 2.86:1 to 2.19:1 regardless of whether the temperature was at 50 or 70 °C, indicating that 6501 and AGS have a very good synergistic effect (Jin et al, , , b, ).…”
Section: Resultssupporting
confidence: 93%
“…After emulsification, most of oil and water separate and the surfactants at the oil–water interface maintain the stability of the emulsion. Due to the combination of oil and KPS hydrophobic groups (Fischer et al, ; Yordanova et al, ), surfactants may remain in the oil phase or form a reverse micelle while demulsifying, which will solubilize the water in oil, resulting in the decrease of surfactants in the water phase.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 11, most of the predicted values agreed well with the experimental data, having an accuracy within 0.5 in the logarithmic scale. The RMSE values are in line with previous studies on octanol−water, 67 micellar systems, 16,21,68 and lipid systems. 17,69,70 Only the partition coefficient for p-nitroaniline was severely underpredicted, with an error considerably higher than 0.5 in the logarithmic scale.…”
Section: ■ Methodsmentioning
confidence: 99%
“…The atomistic level molecular assembly of liquid structure can be achieved by performing molecular dynamics (MD) simulations. The method that combines MD with COSMOmic has been proven to accurately predict partition coefficients of not only homogeneous fluids such as octanol–water but also structured fluids of micelles containing anionic, cationic, and zwitterionic surfactants and surfactants mixtures. …”
Section: Introductionmentioning
confidence: 99%